Southern Cabbageworm (larva), Checkered White (adult) Pontia (=Pieris) protodice (Biosduval & Leconte) (Insecta: Lepidoptera: Pieridae: Pierinae) - Donald W. Hall (EDIS)
EENY-436, a 4-page illustrated fact sheet by Donald W. Hall, is part of the Featured Creatures collection. It describes this pierid butterfly that is common throughout much of the U. S. — its distribution, description, life cycle and biology, host, and economic importance. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.